Digital Doctorates. Issue 1 (27th April 2021) - El Khatib, Randa; Irwin, Reese Alexandra; Winter, Caroline; Levy, Michelle
This essay cluster addresses the curriculum design of graduate programs, asking how Digital Humanities projects might be integrated into them. From the perspectives of M.A. and PhD students, these essays explore the risks and rewards of integrating digital research into a traditional degree program or reshaping the degree requirements altogether. Randa El Khatib opens the cluster with an argument in favour of a digital dissertation, wherein the digital component comprises a significant part of the intellectual work of the dissertation by informing its argument either through the theoretical framework, methodology, or some other significant aspect integral to the original contribution that it makes. Reese Alexandra Irwin considers the institutional and administrative complications of integrating digital research into graduate programs, contending that that the library is the most advantageous place from which to draw support for graduate student digital projects, but that in order for the library to adequately support student projects it must be treated as a pedagogical partner by the student's home department. Caroline Winter uses her experience digitizing Mary Shelley's Gothic tales to explore how developing satellite digital projects that complement monograph-style doctoral dissertations is an opportunity for graduate students to develop digital skills, explore different modes of research, and experience being part of a strong community of practice. In her response, Michelle Levy weighs the risks of the various approaches to digital projects outlined in the previous essays and concludes that the institutions that house these students must offer greater support by adapting to the changing and increasingly digital landscape of humanities disciplines.